On generating efficiency through public-private joint ventures - Udo Broll; Sugata Marjit (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1992)
International joint ventures (JV) are popular institutional forms chosen by the less developed countries (LDCs) to attract foreign Investments. In this paper we describe a set up where a multinational firm (MNF) decides on the volume of investment and the LDC gov-ernment offers a package specifying taxes and sharing rules by a JV contract. Such sharing rules can be designed to enhance the level of optimal investment under the presence of distortions and asymmetric information. We also provide an example where a JV contract might not work. In general, JV contracts lead to efficient outcomes.
Keywords: 330; Internationale Unternehmenskooperation; Multinationales Unternehmen; Auslandsinvestition; Theorie; Entwicklungsländer